Pelatihan dan Praktik Pengelolaan Konten Digital Menggunakan Teknologi Artificial Intelligence (AI) Untuk Meningkatkan Pemasaran Produk UMKM Omah Anjani - Ardian Wahyu Setiawan; Ririn Pratiwi Suharto; Kartika Windrajanti; Eri Widiyanto; Arni Utaminingsih; Evy Fajriantina Lova; Siti Rohani (Prosiding, 2026)
Omah Anjani MSME is a micro business engaged in the production of fabric decorations, bed sheets, and prayer robes, located in Malang. Since its establishment in 2019, this business has had stable production capacity, but its marketing still relies on conventional methods and is not optimal in utilizing digital technology. This community service program aims to improve the MSME team's skills in managing digital marketing based on Artificial Intelligence (AI) technology. The implementation method consists of theoretical and practical training in creating visual content with AI tools, effective copywriting, social media strategies, content data analysis, and collaboration with influencers. This activity is carried out in stages, starting with training in the basics of digital marketing to direct implementation on social media platforms. The expected outcome of this activity is an increase in the understanding and skills of MSME teams in digital marketing management, which will have an impact on increasing brand awareness, expanding market reach, and the competitiveness of MSMEs. In addition, it is also expected that there will be an increase in interaction with the audience through more interesting and relevant content. Through this training, Omah Anjani MSMEs are expected to be able to optimize the use of AI technology to support business growth and strengthen their position in the fabric-based creative industry market.